2021
DOI: 10.1097/rct.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

CT Radiomics for the Prediction of Synchronous Distant Metastasis in Clear Cell Renal Cell Carcinoma

Abstract: The aim of this study was to construct and verify a computed tomography (CT) radiomics model for preoperative prediction of synchronous distant metastasis (SDM) in clear cell renal cell carcinoma (ccRCC) patients.Methods: Overall, 172 patients with ccRCC were enrolled in the present research. Contrast-enhanced CT images were manually sketched, and 2994 quantitative radiomic features were extracted. The radiomic features were then normalized and subjected to hypothesis testing. Least absolute shrinkage and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Compared with MRI, CT has a wider range of uses for the detection, identification, and staging of ccRCC due to its high diagnostic accuracy. A study by Wen et al (18) showed that radiomics features extracted from contrast enhanced CT images demonstrated a good performance for prediction of SDM ccRCC (AUC, 0.83 [95%CI, 0.69-0.95]). However, the weakness of their study is lack of relevant clinical factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with MRI, CT has a wider range of uses for the detection, identification, and staging of ccRCC due to its high diagnostic accuracy. A study by Wen et al (18) showed that radiomics features extracted from contrast enhanced CT images demonstrated a good performance for prediction of SDM ccRCC (AUC, 0.83 [95%CI, 0.69-0.95]). However, the weakness of their study is lack of relevant clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wen et al. ( 18 ) showed that radiomics features extracted from contrast enhanced CT images demonstrated a good performance for prediction of SDM ccRCC (AUC, 0.83 [95%CI, 0.69-0.95]). However, the weakness of their study is lack of relevant clinical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review, only one study analyzed the use of radiomics in predicting distant metastasis. Wen et al examined the role of contrast-enhanced CT images in predicting synchronous distant metastasis in 172 ccRCC patients [ 23 ]. They extracted 2994 quantitative radiomic features and the least absolute shrinkage and selection operator regression was applied for dimension reduction, feature selection, and model construction.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another area of research is predicting prognosis 9 and metastasis. 10,11 A few studies worked on inferring response to targeted therapies of RCC and one prior work tried using radiomics to predict response to immunotherapy. 12,13 These studies are limited by small sample sizes and might not work when novel therapies are introduced.…”
Section: Radiomics Characterization Of Ccrccmentioning
confidence: 99%